Electrocardiography in post hemodialysed chronic kidney disease patients - Soren, Jatin; Majhi, Chakradhar; Patel, Nayan K. (International Journal of Advances in Medicine, 2021)
Background: Chronic kidney disease (CKD) is associated with higher risk of cardiovascular events and Electrocardiographic changes are common in CKD patients. Electrocardiography (ECG) is cheap and easily available investigation that could pick up abnormalities of heart. Our study focuses on electrocardiographic changes seen within 24 hours in post hemodialysis CKD patients. Methods: It is a cross sectional, observational study of 298 CKD patients who underwent hemodialysis at tertiary care facility of VIMSAR, Burla during the period between November 2018 to November 2020. 12 leads ECG of these patients were taken post hemodialysis and abnormalities were interpreted. Results: Total number of patients included in the study were 298 with mean age distribution of 47±8.4 years. Mean Serum urea level was 126 mg/dl. Creatinine levels ranged between 5-10 mg/dl. Left ventricular hypertrophy (LVH) and left atrial enlargement (LAE) were seen in 14.76% and 8.3% of patients respectively. Atrial fibrillation was present in 4.3% of patients. Left axis deviation (LAD 7%), right axis deviation (RAD 6%), atrial ectopics (2.6%) and tall T waves (7.3%) were the other ECG changes observed. Conclusions: ECG changes are common in CKD patients in post hemodialysis state, so it becomes important to monitor these changes in these patients for early detection of any cardiac abnormalities.